Eksplorasi Pengaruh E-WOM dan OCR Terhadap Keputusan Pembelian di Shopee: Perspektif Mahasiswa Ekonomi dan Bisnis Islam Kendari - Jufra, Arlita Aristianingsih; Sauala, Syahvira Dwi Wahyuning (Al-Kharaj: Journal of Islamic Economic and Business, 2024)
This research aims to discover how Electronic Word of Mouth (e-WOM) and Online Consumer Review (OCR) influence people's purchasing choices on Shopee.com. e-WOM and OCR are two other types of information that can help convince people to buy. This research uses primary data as the main source in quantitative methods. This group consisted of 227 respondents selected using the purposive sampling method. Questionnaires sent via Google Forms were used to collect data. Data were analyzed using hypothesis testing, classical hypothesis testing, and multiple linear regression analysis. This study found that e-WOM is significant and positively impacts purchasing choices. The calculated t value of 13.771 is higher than the t table value of 1.970611. This means that e-WOM influences the purchasing choices of students at the Faculty of Economics and Islamic Business, IAIN Kendari. There is a strong relationship between OCR and purchasing choices. The t value of 13.575 is higher than the t table value of 1.970611. This means that OCR also influences students' purchasing decisions at the Islamic Economics and Business Faculty of IAIN Kendari.